Propaganda on demand: Russia’s media environment during the war in Ukraine (Global Media Journal - German Edition, 2023)
In this essay, I explore the nature of propaganda in a hybrid media environment through the example of Russian propaganda during the ongoing war in Ukraine. I start by briefly overviewing the Russian media system’s development, focusing on the roots of cynical attitude toward journalism in the society. After analyzing propaganda strategies, I suggest the propaganda on demand concept, which describes the manipulation of public opinion by targeting different social milieus with specifically tailored narratives. In Russia’s case, this approach is based on inconsistency and eclecticism. However, it seems well suited to the very logic of the digital realm, which helps the state deliver often-contradicting narratives to different target groups.
Keywords: propaganda; digital media; Russia-Ukraine war; Russian media